“Dosis de fertilizante con microorganismos benéficiosos (ferti em) en el cultivo de un ecotipo de tomate (lycopersicum esculentum mill.), en el distrito de Lamas-Región San Martín” - Pino Rojas, Jaime Micolas (2015)
This research aimed to evaluate and determine the most effective dese of fertilizar with beneficia! microorganisms (EM Ferti) in crop yield an ecotype of tomate (Lycopersicum esculentum Mill.) District Lamas and perform economic analysis of the treatments under study. The research was conducted on the grounds of the Fundo "The Pacific" owned by Mr. Jorge Luis Pelaez Rivera, politically located in the district and province of Lamas, San Martin department. The statistical design of randomized complete block (RCBD) with three replications and five treatments, with a total of 15 experimental units was used. The information gathered in the field was processed using SPSS 19 statistical software, which uses the P-value as meaningful comparison to the confidence levels of 0.05 and 0.01 differences in the analysis of variance (ANOVA) and multiple range test of Duncan P